Trachea and Laryngeal Rupture Induced Pneumomediastinum in Psychiatric Patients : A Case Report - Wa Ode Zerbarani; Sri Asriyani; Eny Sanre (Jambura Medical and Health Science Journal, 2022)
Introduction: Laryngeal rupture is a potentially life-threatening aerodigestive injury, especially in cases with slow treatment, which can occur spontaneously, iatrogenic or as a result of trauma.Case: We present a case of pneumomediastinum due to sharp trauma causing a laryngeal rupture in a patient with psychiatric disorders. Pneumomediastinum is one of the complications that occur.Discussion: Trauma history and clinical complaints are very helpful in establishing the diagnosis, and imaging has an important role in describing pneumomediastinum and other air leak syndromes so that early treatment can be done immediately.Conclusion: The approach to diagnosing pneumomediastinum with imaging in psychiatric patients has an important role because of the lack of information about complaints and mechanisms of pneumomediastinum.